2021
DOI: 10.48550/arxiv.2108.01672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Varstrometry for Off-nucleus and Dual sub-Kpc AGN (VODKA): Hubble Space Telescope Discovers Double Quasars

Yu-Ching Chen,
Hsiang-Chih Hwang,
Yue Shen
et al.

Abstract: Dual supermassive black holes (SMBHs) at ∼ kpc scales are the progenitor population of SMBH mergers and play an important role in understanding the pairing and dynamical evolution of massive black holes in galaxy mergers. Because of the stringent resolution requirement and the apparent rareness of these small-separation pairs, there are scarce observational constraints on this population, with few confirmed dual SMBHs at < 10 kpc separations at z > 1. Here we present results from a pilot search for kpc-scale d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Few such binaries are known to exist during 'cosmic noon' -the peak of quasar activity. Chen et al (2021) provide a compilation of known binary quasars and candidates, with only one sub-10-kpc confirmed system above z = 1: SDSSJ1238+0105, a BAL+non-BAL quasar pair at z = 3.13 separated by 7.8 kpc, confirmed by Tang et al (2021) (we note that SDSSJ0818+0601 from More et al 2016 has subsequently been confirmed as a lensed quasar by Hutsemékers et al 2020, and J2057+0217 from Lemon et al 2018 is potentially also a lensed quasar). Two further systems from the literature are likely real binary quasars due to their differing spectra: DESJ0120−4354 (7.2 kpc at z = 1.91, Anguita et al 2018), and SDSS J1008+0351 (9.4 kpc at z = 1.74, Inada et al 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Few such binaries are known to exist during 'cosmic noon' -the peak of quasar activity. Chen et al (2021) provide a compilation of known binary quasars and candidates, with only one sub-10-kpc confirmed system above z = 1: SDSSJ1238+0105, a BAL+non-BAL quasar pair at z = 3.13 separated by 7.8 kpc, confirmed by Tang et al (2021) (we note that SDSSJ0818+0601 from More et al 2016 has subsequently been confirmed as a lensed quasar by Hutsemékers et al 2020, and J2057+0217 from Lemon et al 2018 is potentially also a lensed quasar). Two further systems from the literature are likely real binary quasars due to their differing spectra: DESJ0120−4354 (7.2 kpc at z = 1.91, Anguita et al 2018), and SDSS J1008+0351 (9.4 kpc at z = 1.74, Inada et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Thanks to dedicated spectroscopic confirmation campaigns in recent years, the clustering amplitude is well-measured above ∼25 kpc up to z ≈ 2, that is, with sky separations above 3 arcseconds (Hennawi et al 2010;Kayo & Oguri 2012;Eftekharzadeh et al 2017). However, probing the final stages of mergers at the peak of quasar activity (z ∼ 2−3) requires yet smaller separation binaries at higher redshifts, of which very few are known (see Chen et al 2021 for a compilation of redshift and separations of known systems and candidates). Both observations and simulations link increased quasar activity with decreasing merger separation, peaking below 10 kpc, suggesting a similar peak should be seen for binary quasars (Van Wassenhove et al 2012;Capelo et al 2017;Stemo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Few such binaries are known to exist during 'cosmic noon' -the peak of quasar activity. Chen et al (2021) provide a compilation of known binary quasars and candidates, with only one sub-10-kpc confirmed system above z = 1: SDSSJ1238+0105, a BAL+non-BAL quasar pair at z = 3.13 separated by 7.8 kpc, confirmed by Tang et al (2021) (note that SDSSJ0818+0601 from More et al (2016) has subsequently been confirmed as a lensed quasar by Hutsemékers et al (2020), and J2057+0217 from Lemon et al (2018) is potentially also a lensed quasar). Two further systems from the literature are likely real binary quasars due to their differing spectra: DESJ0120−4354 (7.2 kpc at z = 1.91, Anguita et al 2018), and SDSS J1008+0351 (9.4 kpc at z = 1.74, Inada et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to dedicated spectroscopic confirmation campaigns in recent years, the clustering amplitude is well-measured above ∼25 kpc up to z ≈ 2, i.e., sky separations above 3 arcseconds (Hennawi et al 2010;Kayo & Oguri 2012;Eftekharzadeh et al 2017). However, probing the final stages of mergers at the the peak of quasar activity (z ∼ 2−3) requires yet smaller separation binaries at higher redshifts, of which very few are known (see Chen et al 2021 for a compilation of redshift and separations of known systems and candidates). Both observations and simulations link increased quasar activity with decreasing merger separation, peaking below 10 kpc, suggesting a similar peak should be seen for binary quasars (Van Wassenhove et al 2012;Capelo et al 2017;Stemo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is practicable that the detection algorithm could identify blended pairs even if the separation is below the typical angular resolution. Chen et al (2021) recently reported tens of the sub-arcsec dual quasar candidates discovered in the Hubble Space Telescope. A significant fraction of those sub-arcsec pairs are identified as two sources in the DECaLS catalog, showing possible source identification even below angular resolution.…”
Section: Comparison To Previous Work and Implications On Future Surveysmentioning
confidence: 99%